(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
How heavy is the weight of Matthew (Matteo) Ricci in Chinese culture or, in other words, did Matthew Ricci succeed in his attempt to be Li Madou? The crucial question begins with the language competence Ricci and the Fathers of his mission acquired in Mandarin and continues with the double-faced encounter on the ground of human understanding and religious persuasion. This paper aims at outlining some of the basic questions posited by the first experiment, in order to make up a cross-cultural dialogue involving philosophical, scientific and religious matters. The three parts of the paper focus on: a) the newly experimented inculturative policy aimed at persuading the Chinese literati about the feasibility of an intercultural exchange; b) the viability of a linguistic experimentation through which communication of mutual knowledge could be attempted; c) the relationship between the apostolic message and the three religions of China. Keywords: Matthew (Matteo) Ricci; Cultures in contact; Missiology; Renaissance; Western and Eastern studies.